2020
DOI: 10.3390/polym12091910
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Dominated Copper Salicyaldimine Complexes—Structures, Coordination Mode of Nitrate and Decolorization Properties toward Acid Orange 7 Dye

Meng-Jung Tsai,
Chi-Jou Tsai,
Ken Lin
et al.

Abstract: A salicyaldimine ligand, 3-tert-butyl-4-hydroxy-5-(((pyridin-2-ylmethyl)imino)methyl)benzoic acid (H2Lsalpyca) and two Cu(II)−salicylaldimine complexes, [Cu(HLsalpyca)Cl] (1) and [Cu(HLsalpyca)(NO3)]n (2), have been synthesized. Complex 1 has a discrete mononuclear structure, in which the Cu(II) center is in a distorted square-planar geometry made up of one HLsalpyca− monoanion in an NNO tris-chelating mode and one Cl− anion. Complex 2 adopts a neutral one-dimensional zigzag chain structure propagating along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…51,52 In addition, the e − also combines with O 2 in the system to form super-oxide radicals (˙O 2 − ). 53 Moreover, Fei 54 and Wang 55 demonstrated that ˙OH, O 2 − and h + are the main reactive species during the degradation of MO. So, the degradation mechanism of MO can be expressed by the following reactions: 56,57 1 or 2 + hv → h + + e − h + + H 2 O or H 2 O 2 → ˙OH + H + e − + O 2 → ˙O 2 − ˙OH or ˙O 2 − + MO → Products…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52 In addition, the e − also combines with O 2 in the system to form super-oxide radicals (˙O 2 − ). 53 Moreover, Fei 54 and Wang 55 demonstrated that ˙OH, O 2 − and h + are the main reactive species during the degradation of MO. So, the degradation mechanism of MO can be expressed by the following reactions: 56,57 1 or 2 + hv → h + + e − h + + H 2 O or H 2 O 2 → ˙OH + H + e − + O 2 → ˙O 2 − ˙OH or ˙O 2 − + MO → Products…”
Section: Resultsmentioning
confidence: 99%
“…51,52 In addition, the e − also combines with O 2 in the system to form superoxide radicals (˙O 2 − ). 53 Moreover, Fei 54 All in all, 1 and 2 exhibited good photocatalytic activities for the degradation of MO in combination with H 2 O 2 under the irradiation of sunlight, and the photocatalytic effect of 1 was better than that of 2, which corresponds to their E g values.…”
Section: Crystengcomm Papermentioning
confidence: 93%